(untitled) (Indian Journal of Public Health Research & Development, 2020)
Background: Communication is a key element in providing high quality health care services, leading to patient satisfaction and better health. Patient- centered communication is a basic component of nursing and facilitates development of positive nurse-patient relationship. Objectives:1) To determine barriers of communication between nurses and patients 2) To provide evidence based recommendations. Materials and Methods: A descriptive cross sectional study was conducted among 100 nurses & 50 patients during May to July 2019. Separate questionnaires were used for nurses and patients containing socio-demographic details and barriers of communication along with open ended questions. Results: All the nurses were females.85% were in the age group of 21-30 years. Majority of patients were either 21-30 years (36%) or >40 years (36%). 52% of the patients were females. Unpleasant experience in past with patients (mean score-4.11) and use of technical terms by the nurses (mean score-3.28) were main perceived barriers to effective communication among Nurses and patients respectively. Thematic analysis of open ended questions revealed some important barriers and ways to overcome it, such as more staff recruitment, provision of enough time to know the patient, patient’s sensitization with their assigned nurses and hospital environment, regular training in communication skills. Conclusion: Unpleasant experiences in past and use of medical jargons were the important one among many as perceived by nurses and patients respectively, which can be tackled by effective communication training of nurses, sensitization programme for patients and increasing the nurses: patient ratio as suggested by the participants.